Albuminuria and Primary Open-Angle Glaucoma: the Singapore Chinese Eye Study (SCES). Issue 5 (16th July 2020) - Lim, Zhi Wei; Chee, Miao-Li; Thakur, Sahil; Fang, Xiaoling; Soh, Zhi Da; Majithia, Shivani; Teo, Zhen Ling; Sabanayagam, Charumathi; Wong, Tien Yin; Cheng, Ching-Yu; Tham, Yih-Chung
Abstract : Aims: To determine the association between albuminuria and primary open-angle glaucoma (POAG). Methods: Participants of the Singapore Chinese Eye study were recruited and underwent standardised ocular and systemic examinations. Albuminuria was determined using urinary albumin-to-creatinine ratio (UACR, mg/g) based on random spot urinary albumin and creatinine measurements. POAG was defined using the International Society of Geographic and Epidemiological Ophthalmology classification. Multivariable logistic regression with generalised estimating equation model was used to evaluate the association between albuminuria and POAG, while accounting for correlation between eyes. Results: A total of 3009 Chinese adults (5963 eyes), aged 40–80 years, were included in this study, of which, 52 subjects (75 eyes) had POAG. Higher UACR (per 50 mg/g increase) was independently associated with POAG (OR=1.04, 95% CI 1.01 to 1.07, p=0.003) following adjustment for age, gender, intraocular pressure, diabetes mellitus, hyperlipidaemia, hypertension, anti-hypertensive medication, history of cardiovascular disease, current smoking status, alcohol intake, body mass index and estimated glomerular filtration rate. Further stratification revealed that individuals with macroalbuminuria were 8.00 times likely to have POAG (95% CI 2.97 to 21.54, p<0.001), compared with those with normoalbuminuria. Microalbuminuria was not significantly associated with POAG (OR=0.49, 95% CI 0.19 to 1.29, p=0.150). The association between macroalbuminuria and POAG remained significant among individuals who were diabetic (OR=9.89, 95% CI 2.49 to 39.30, p=0.001) and hypertensive (OR=8.39, 95% CI 3.07 to 22.94, p<0.001). Conclusion: In this population-based study of Chinese adults, albuminuria was independently associated with POAG. Our findings provide further understanding on the pathogenesis of POAG and may potentially help to better identify individuals at risk of POAG.